Revisiting Criminal Policy: Between Prevention, Rehabilitation, and Restorative Justice - Yusep Mulyana (PT. Anagata Sembagi Education, 2025)
Criminal justice policy in Indonesia continues to be dominated by the deterrence paradigm, which emphasizes the deterrent effect of severe punishment. This is evident in the increasing overcrowding of correctional institutions, which are operating at more than twice their normal capacity, and the high rate of recidivism. This study aims to review the direction of Indonesia's criminal justice policy by examining the interaction between three main paradigms, namely deterrence, rehabilitation, and restorative justice, in the context of national social and political change. Using a qualitative approach with a descriptive-analytical design based on socio-legal research, this study analyzes legal documents, official institutional data, and interviews with legal experts and practitioners from the period 2015–2024. The results of the study show that Indonesian criminal policy is still influenced by penal populism and political pressure, although there are indications of a shift towards a more humanistic paradigm through the application of restorative justice. However, this transition is still partial and faces institutional resistance and resource constraints in its implementation in the field. This study concludes that the success of criminal policy reform in Indonesia requires political balance in penal policy, namely a balance between political power, public interest, and human values in the formulation of criminal law. These findings are expected to serve as a conceptual basis for the renewal of a more just, effective, and sustainable criminal justice system.